POTENSI KULIT DURIAN SEBAGAI SUMBER ENERGI ALTERNATIF MELALUI PEMBUATAN BRIKET - Muhamad Habib Nurwahdan; Susilawati; Dimas Septiadi; Muhammad Husin Pangaribuan; Iswar Saputra Nasution; Afzidan Luthfi Amaryu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The accumulation of durian peel waste has become an environmental problem due to its large volume and limited utilization, while energy demand continues to increase. This study aims to examine the potential of durian peel waste as a raw material for charcoal briquettes as an alternative and environmentally friendly fuel. This research employed a qualitative descriptive method with observational and literature study approaches. The research process involved observing the stages of briquette production, including drying, carbonization, grinding, mixing with a binder, molding, and drying. The results showed that durian peel waste could be processed into charcoal briquettes with good physical characteristics, such as compact structure, uniform shape, and sufficient durability. The produced briquettes were able to ignite easily and generate stable heat, indicating their potential use as an alternative household fuel. This study concludes that utilizing durian peel waste into charcoal briquettes can reduce biomass waste and provide added value as a renewable energy source. Further studies are recommended to conduct quantitative laboratory testing to improve product quality and assess its feasibility for larger-scale production.